2015
DOI: 10.1186/s12885-015-1985-3
|View full text |Cite
|
Sign up to set email alerts
|

Lgr5 expression is a valuable prognostic factor for colorectal cancer: evidence from a meta-analysis

Abstract: BackgroundLgr5 has recently been identified as a reliable biomarker of cancer stem cells (CSCs) in colorectal cancer (CRC); however, its prognostic value is still controversial.MethodsWe searched PubMed, Web of Science, and Wanfang databases with identical strategies to retrieve articles. We evaluated the impact of Lgr5 expression on survival of CRC patients through meta-analysis.ResultsA total of 12 studies comprising 2600 patients revealed that Lgr5 overexpression was negatively associated with overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Recently, high LGR5 expression has been reported in CRC-invading cells, which was characterized by high CD44 and low KRT20 expression, combined with a remarkable increase in the stem cell population [Baker et al 2015]. In CRC, high LGR5 protein expression has also been associated with high risk of relapse, decrease of disease-free survival, and high rate of hepatic and lymph node metastases [Jiang et al 2016].…”
Section: Prognostic and Predictive Stemness Biomarkersmentioning
confidence: 99%
“…Recently, high LGR5 expression has been reported in CRC-invading cells, which was characterized by high CD44 and low KRT20 expression, combined with a remarkable increase in the stem cell population [Baker et al 2015]. In CRC, high LGR5 protein expression has also been associated with high risk of relapse, decrease of disease-free survival, and high rate of hepatic and lymph node metastases [Jiang et al 2016].…”
Section: Prognostic and Predictive Stemness Biomarkersmentioning
confidence: 99%
“…In colorectal cancer, LGR5 is overexpressed in adenomas and frequently found in metastatic tissue, correlating with poor prognosis [103,[111][112][113][114]. These reports are in line with two meta-analysis studies on colorectal cancer, in which LGR5 has been proposed as a poor prognosis marker [115,116]. Not yet explained is the clear controversy between multiple studies regarding the precise function of LGR5 (activator or negative regulator?)…”
Section: Prognostic Value Of Lgrsmentioning
confidence: 70%
“…By integrating the outcome data from all the currently available studies, our meta-analysis showed that mTOR could be a strong biomarker for poor prognosis of ESCC, because that a prognostic marker would be considered of high predictive value for the negative prognosis if its HR value was larger than 2 [25, 28]. Remarkably, further subgroup analyses indicated that such relationships between mTOR/p-mTOR expression and worse survival of ESCC were not substantially altered by different endpoints, cut-off values and follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Consulting similar meta-analyses addressing on the prognostic value of biomarkers [25, 26, 28], we combined the following six key words with Boolean Operators (“AND” and “OR”), including four “esophageal cancer” terms and two “mTOR” terms, to formulate two search strings in each selected database. These key words are listed as follows:

Esophageal cancer terms: “esophageal cancer”, “esophageal carcinoma”, “esophageal neoplasm” and “esophageal malignancy”;

mTOR terms: “mammalian target of rapamycin” and “mTOR”.

…”
Section: Methodsmentioning
confidence: 99%